Per- and polyfluorinated substances (PFASs): Environmental challenges - Krafft, Marie Pierre; Riess, Jean G. (Current opinion in colloid & interface science, 2015)
Long-chain perfluoroalkylated acids are persistent in the environment, leading to ubiquitous exposure of biota. They have been listed as very persistent, very bioaccumulative and toxic by Public Health Authorities. Their production and use have been regulated in most western countries but their production has increased in other geographical area. Animal studies show highly diverse and complex, product-, species- and gender-dependent pharmacodynamics and toxicity profiles. Human epidemiologic studies unveiled liver, developmental and other adverse health effects, while further effects remain inconclusive. Alternative short-chain products are technically much less performing. Alternative long-chain processing aids have not been proven environmentally advantageous. Risk assessment is difficult and highly uncertain. Little breakthrough products or technologies have yet emerged that can match the feats of fluorinated surfactants and fluorinated polymers. Radical, disruptive new solutions are needed. Meanwhile, more reasonable, more selective use of these compounds appears indispensable in order to reduce exposure while preserving their societal benefits and without penalizing developing countries. Progress in the risk management of per- and polyfluorinated substances is, however, impeded by considerable knowledge and information gaps, and will demand sustained multidisciplinary efforts. [Display omitted] •Globally persistent, bioaccumulating, toxic perfluoroalkyl acids are now regulated.•Numerous untoward effects are seen in animal models.•Humans are exposed worldwide, experience health effects, often inconsistently.•Global production is still increasing and present alternatives are not satisfactory.•Better understanding, information, responsible use, breakthrough technologies are needed.